The impact of breast augmentation on the skin temperature of the breast - Piščević, Branislav; Brdareski, Zorica; Stepić, Nenad; Djordjević, Boban; Vulović, Dejana; Jovanović, Marko; Vulović, Dejan (Vojnosanitetski pregled, 2021)
AbstractIntroduce and aimComplications of breast augmentation, as one of the most common cosmetic surgery, may be different. Besides the usual early, local postoperative complications, the most common late complication is capsular contracture. As a specific complications of skin functions after this operation only disturbance of sensibility is described. Since the skin has other functions as well, and because there are no literature data available, we decided that the goal of the research is measuring the temperature of skin temperature before and after surgery. MethodsA prospective interventional study was done in 49 adult women. Bilateral augmentative mammaplasty was performed for breast hypoplasia or on the personal request of a patient with eutrophic breasts. Measuring of the temperature of the skin of the breast was done in two points, before the operation, seven days after surgery and three months after surgery. Temperature measurement was done by infrared thermometer (Pyrometer TROTEC BP21). Statistic significance was determined using the t- test for related samples. Differences were considered statistically significant if p was less than 0.05. Eta squared coefficient was determined by the size and impact criteria Cohen all over 12:14 signified a major impact. The data were analyzed by IBM SPSS Statistics v20. ResultsIn the majority of patients breasts were hypoplastic (69.39%). The most commonly used implants were 275-500ml volume (46.94%), and the least common implants were over 500ml (16.33%). In a little less than 2/3 of the patientssubmammary incision was used (61.22%). In the majority of patients (67.35%), prosthesis were placed subglandular. The average value of the temperature before the operation at point 1 was 34.49° C, seven days after surgery 34.81° C, and three months after surgery 34.10 ° C; and in item 2: 34.60° C, 34.91° C and 34.19° C in the same time intervals. In relation to the size of the breast before operation, and the size of the implant manufacturer, the localization of the incision and placement of the localization of the prosthesis, had no statistically significant differences in the temperature of the skin of the breast before and after surgery.ConclusionOur results on the change of skin temperature after breast augmentation could have significance in preoperative patient information Key words: Breast augmentation, complications , skin temperature, breast temperature   Background/Aim. Complications of breast augmentation, as one of the most common cosmetic surgery, may be different. Besides usual early, local postoperative complicatons, the most common late complication is capsular contracture. As a specific complication of skin functions after this operation only disturbance of sensibility is described. Since the skin has other functions as well, and because there are no literature data available, the aim of this research was measuring the skin temperature before and after surgery. Methods. A prospective intervential study was done in 49 adult women. Bilateral augmentative mammaplasty was performed for breast hypoplasia or on the personal request of a patient with autrophic breasts. Measuring the temperature of the breast skin was done in two points, before the operation, and seven days and three months after surgery. The temperature measurement was done by the infrared thermometer (Pyrometer TROTEC BP21). Statistically significant difference was determined using the t-test for related samples. Differences were considered statistically significant if p was less than 0.05. Eta squared coefficient was use to determine the import size and according to the Cohen criteria everything over 10:14 signified a major impact. The data were analyzed by the IBP SPSS Statistics v20. Results. In a majority of patients the breasts were hypoplastic (69.39%). The most commonly used implants were 275–500 mL volume (46.94%), and the least common implants were over 500 mL (16.33%). In a little less than 2/3 of the patients submammary incision was used (61.22%). In a majority of patients (67.35%) the prosthesis were placed subglandularly. The average value of the temperature before the operation at the point 1 was 34.49ºC, seven days after surgery 34.81ºC, and three months after surgery 34.10ºC; and at the point 2: 34.60 ºC, 34.91ºC and 34.19ºC in the same time intervals. In relation to the size of the breasts before operation and the size of the implant manufacturer, the localization of the incision and placement of the localization of the prosthesis, no statistically significant differences in the temperature of the skin of the breast before and after surgery was observed. Conclusion. Our results on the change of skin temperature after the breast augmentation could be significant preoperative information for the patients.
Keywords: breast implantation; reconstructive surgical procedures; skin temperature; treatment outcome.